High-strength micro motor rotor and preparation method thereof

By optimizing material formulation and manufacturing processes, improving the physical strength, magnetic properties, wear resistance and thermal conductivity of micro motor rotors, the problem of degradation of existing motor rotors under high load and high speed is solved, and the performance of existing motor rotors is achieved longer Lifespan and higher motor performance.

CN119392124APending Publication Date: 2025-02-07ZEB (NINGBO) PRECISION ELECTROMECHANICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411489600.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing motor rotors have problems such as insufficient physical strength, uneven magnetic field distribution, poor wear resistance and poor thermal conductivity under high load and high speed, resulting in shorter service life, increased maintenance costs and reduced motor performance.

Method used

Optimized material formulations, including fine magnetic powder, isopropanol, polyvinyl alcohol, zinc stearate, borax, graphite, rare metals, aluminum alloy powder, nickel alloy powder, carbon fiber and nanoceramics, through ball milling, pre-magnetization, sintering and strengthen magnetic charging and other processes to improve the physical strength, magnetic properties, wear resistance and thermal conductivity of the rotor.

Benefits of technology

It significantly improves the comprehensive performance of the micro motor rotor, extends the service life, reduces maintenance costs, and improves the stability and efficiency of the motor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099653930000071
    Figure BDA0005099653930000071
  • Figure BDA0005099653930000081
    Figure BDA0005099653930000081
Patent Text Reader

Abstract

The invention belongs to the technical field of motors, and relates to a high-strength micro motor rotor and a preparation method thereof. According to the high-strength micro motor rotor, the comprehensive performance of the rotor is remarkably improved by optimizing the material formula and the manufacturing process, the physical strength and rigidity of the rotor are remarkably improved by mixing the aluminum alloy powder and the nickel alloy powder with different granularities and adding the carbon fibers and the nano ceramic particles, and the service life of the rotor is prolonged. The addition of rare metals further enhances the wear resistance and corrosion resistance of the material, and prolongs the service life of the rotor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of motors and relates to a high-strength micro motor rotor and a preparation method thereof. Background Art

[0002] The rotor is one of the core components in the motor. Its main function is to convert electrical energy into mechanical energy to drive the movement of the motor. However, existing motor rotors have deficiencies in many aspects. These problems not only affect the overall performance of the motor, but also limit its application in high-load and high-speed environments. First of all, insufficient physical strength is a major problem. Existing rotor materials are prone to fatigue damage under high loads and high speeds, resulting in a shortened service life. The material's strength and rigidity are insufficient to withstand long-term high-speed operation and impact, which is particularly evident in industrial applications, especially in situations where long-term continuous operation is required. Fatigue damage to the rotor will lead to frequent repairs and replacements, increasing maintenance costs and downtime.

[0003] Uneven magnetic field distribution is also a significant problem. In traditional manufacturing methods, the uniformity and consistency of materials are poor, resulting in uneven magnetic field distribution inside the rotor, affecting the performance and efficiency of the motor. Unevenness during pre-magnetization and magnetization can also lead to uneven magnetic field distribution, which in turn affects the running smoothness and noise level of the motor. This uneven magnetic field distribution not only reduces the efficiency of the motor, but may also cause additional vibration and noise during the operation of the motor, affecting its stability and reliability.

[0004] In addition, poor wear resistance is also an important problem of existing motor rotors. Existing rotor materials have insufficient wear resistance and are prone to wear during long-term operation, affecting the stability and life of the motor. The debris generated by wear may cause damage to other components inside the motor, further increasing the failure rate of the motor. Especially in high-load and high-speed applications, the wear problem of the rotor is particularly prominent, which not only affects the performance of the motor, but also increases the cost of maintenance and replacement.

[0005] Another problem is poor thermal conductivity. Existing rotor materials have poor thermal conductivity, which leads to heat accumulation, affecting the heat dissipation effect of the motor, thereby reducing the efficiency and life of the motor. Under high load and high speed operating conditions, the temperature of the rotor will rise rapidly. If the thermal conductivity is poor, the heat cannot be effectively dissipated, causing the motor to overheat or even damage. This not only affects the normal operation of the motor, but may also cause safety hazards. Summary of the invention

[0006] The purpose of the present invention is to address the above problems existing in the prior art and to provide a high-strength micro motor rotor with excellent physical strength, rigidity, wear resistance and corrosion resistance.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A high-strength micro motor rotor, characterized in that the micro motor rotor comprises the following raw materials in parts by mass: 90-95 parts of fine magnetic powder, 7-8 parts of isopropyl alcohol, 5-6 parts of polyvinyl alcohol, 6-7 parts of zinc stearate, 0.4-0.5 parts of borax, 0.3-0.5 parts of graphite, 1.5-3 parts of rare metals, 6-8 parts of aluminum alloy powder, 5-10 parts of nickel alloy powder, 1-2 parts of carbon fiber, and 0.5-14 parts of nano ceramics.

[0009] In the above-mentioned high-strength micro-motor rotor, the rare metals are molybdenum, tantalum, and zirconium in a mass ratio of 1: (0.5-2): (0.5-2). The addition of the three rare metals of the present invention can significantly improve the hardness and wear resistance of the material. The high hardness characteristics of molybdenum and tantalum can reduce the wear of the material during long-term operation and extend the service life of the rotor. The oxidation resistance of zirconium can also reduce the oxidation wear of the material at high temperatures and further improve the wear resistance; these rare metals have good thermal conductivity, which can improve the thermal conductivity of the rotor, reduce heat accumulation, and improve the heat dissipation effect of the motor. The high thermal conductivity of molybdenum and tantalum can effectively dissipate the heat generated by the rotor during operation, prevent overheating, and improve the efficiency and life of the motor. The high temperature stability of zirconium also helps to maintain good thermal conductivity in high temperature environments; and it can improve the magnetic properties of the rotor and improve the magnetic permeability and magnetic saturation of the rotor. The high magnetic permeability characteristics of molybdenum and tantalum can enhance the conduction effect of the magnetic field and improve the efficiency of the motor. The addition of zirconium can improve the magnetic stability of the material and ensure the uniformity and stability of the magnetic field distribution.

[0010] In the above-mentioned high-strength micro motor rotor, the aluminum alloy powder is a mixed powder of aluminum alloy with a particle size of 50-70 μm and a particle size of 0.5-10 μm in a mass ratio of 1: (0.2-0.4).

[0011] In the above-mentioned high-strength micro motor rotor, the nickel alloy powder is a mixed powder of nickel alloy with a particle size of 30-40 μm and a particle size of 0.3-15 μm in a mass ratio of 1: (0.1-0.3).

[0012] The present invention can significantly improve the filling density of the powder by mixing aluminum alloy powder and nickel alloy powder of different particle sizes. The powder with a larger particle size can fill the gaps between large particles, while the powder with a smaller particle size can further fill the fine gaps, thereby making the overall filling density of the powder higher. High filling density means that more materials are effectively utilized, which improves the densification degree of the material during the sintering process, reduces the porosity, and thus improves the physical strength and mechanical properties of the rotor. Aluminum alloy powder has good thermal conductivity. The mixed use of different particle sizes can further improve the thermal conductivity of the material. The powder with a larger particle size provides a good thermal conduction path, while the powder with a smaller particle size fills the gaps, reduces thermal resistance, and improves the overall thermal conduction effect. Nickel alloy powder has good thermal conductivity and stability at high temperatures. The mixed use of different particle sizes can further improve the high-temperature thermal conductivity of the material, ensuring the stable operation of the rotor under high load and high speed. By adding two kinds of aluminum alloy powder and nickel alloy powder with different particle sizes, the filling density, sintering performance, physical strength, thermal conductivity and magnetic properties of the micro motor rotor can be significantly improved. These optimization measures ensure the stability and reliability of the rotor under high load and high speed, extend its service life and improve the overall performance of the motor.

[0013] The present invention also provides a method for preparing the high-strength micro-motor rotor, the method comprising the following steps:

[0014] S1, prepare the above raw materials;

[0015] S2, mixing fine magnetic powder, isopropyl alcohol, polyvinyl alcohol, zinc stearate, borax, graphite, molybdenum, tantalum, zirconium, aluminum alloy powder, nickel alloy powder, carbon fiber and nano-ceramic particles uniformly, and then ball milling to obtain powder;

[0016] S3, pre-magnetizing the powder, then sintering it, and then cooling it to room temperature;

[0017] S4, finally carry out enhanced magnetization.

[0018] In the above-mentioned method for preparing a high-strength micro motor rotor, the ball milling treatment uses a planetary ball mill, wherein the ball-to-material ratio is (3-8):1, the ball milling speed is 250-350r / min, and the time is 80-100min.

[0019] In the above-mentioned method for preparing a high-strength micro motor rotor, pre-magnetization is specifically as follows: placing the powder in a mold and applying a magnetic field of 8000-10000GS, and cold pressing with a falling pressure head, with a holding time of 1-3s.

[0020] In the above method for preparing a high-strength micro-motor rotor, the sintering temperature is 950-110° C. and the sintering time is 4-10 min.

[0021] In the above-mentioned method for preparing a high-strength micro-motor rotor, the cooling rate needs to be controlled at 50-60° C. / s during the cooling process in step S3.

[0022] In the above-mentioned method for preparing a high-strength micro-motor rotor, a magnetic field of 10000-12000 GS is applied during the enhanced magnetization process for 5-10 seconds at a temperature of 50-60°C.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The high-strength micro-motor rotor of the present invention significantly improves the comprehensive performance of the rotor by optimizing the material formula and manufacturing process. By mixing aluminum alloy powder and nickel alloy powder of different particle sizes, and adding carbon fiber and nano-ceramic particles, the physical strength and rigidity of the rotor are significantly improved. The addition of rare metals further enhances the wear resistance and corrosion resistance of the material, thereby improving the service life of the rotor.

[0025] 2. The uniformly mixed powder and multiple cold pressing pre-magnetization of the present invention ensure the uniformity of the magnetic field distribution inside the rotor, thereby improving the operating efficiency and stability of the motor.

[0026] 3. The present invention applies a magnetic field of 10000-12000GS during the enhanced magnetization process for 5-10s at a temperature of 50-60°C, which further improves the magnetic properties of the rotor. The present invention significantly improves the physical strength, magnetic field distribution uniformity, wear resistance, thermal conductivity and production efficiency of the micro motor rotor by optimizing materials and processes, ensuring that it has higher reliability and longer service life in practical applications. DETAILED DESCRIPTION

[0027] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0028] Embodiment 1:

[0029] S1. Prepare the following raw materials: 94 parts of fine magnetic powder, 7 parts of isopropyl alcohol, 6 parts of polyvinyl alcohol, 7 parts of zinc stearate, 0.45 parts of borax, 0.4 parts of graphite, 3 parts of rare metals, 7 parts of aluminum alloy powder, 5 parts of nickel alloy powder, 2 parts of carbon fiber, and 5 parts of nano-ceramics;

[0030] The fine magnetic powder was purchased from Baosteel Tiantong Magnetics Co., Ltd.

[0031] The rare metals are molybdenum, tantalum and zirconium in a mass ratio of 1:1:1;

[0032] The aluminum alloy powder is a mixed powder of aluminum alloy with a particle size of 55 μm and a particle size of 0.5 μm in a mass ratio of 1:0.3;

[0033] The nickel alloy powder is a mixed powder of a nickel alloy having a particle size of 38 μm and a particle size of 5 μm in a mass ratio of 1:0.2;

[0034] S2, fine magnetic powder, isopropyl alcohol, polyvinyl alcohol, zinc stearate, borax, graphite, molybdenum, tantalum, zirconium, aluminum alloy powder, nickel alloy powder, carbon fiber and nano-ceramic particles are mixed uniformly, and then ball milled using a planetary ball mill with a ball-to-material ratio of 5:1, a rotation speed of 300 r / min, and a duration of 90 min;

[0035] S3, placing the powder in a mold in a press, applying a 10000GS magnetic field for pre-magnetization, and dropping the pressure head for cold pressing. The holding time is 2s, and the filling and cold pressing are repeated three times;

[0036] S4, when the vacuum degree is less than 0.01Pa, the mold is heated to 1000℃, then kept warm for 8min, and then cooled to room temperature at a rate of 55℃ / s;

[0037] S5, performing rough grinding and fine grinding on the end face and outer cylindrical surface of the sintered rotor magnetic column, placing the finished rotor magnetic column after grinding in the mold of an injection molding machine, and performing injection molding to obtain a complete motor rotor;

[0038] S6. Place the molded rotor in a 10000GS magnetic field at 55°C for enhanced magnetization, and perform surface deburring on the magnetized rotor to ensure a smooth surface of the finished product.

[0039] Embodiment 2:

[0040] S1. Prepare the following raw materials: 90 parts of fine magnetic powder, 7 parts of isopropyl alcohol, 5 parts of polyvinyl alcohol, 6 parts of zinc stearate, 0.4 parts of borax, 0.4 parts of graphite, 1.5 parts of rare metals, 6 parts of aluminum alloy powder, 5 parts of nickel alloy powder, 1 part of carbon fiber, and 0.5 parts of nano-ceramics;

[0041] The fine magnetic powder was purchased from Baosteel Tiantong Magnetics Co., Ltd.

[0042] The rare metals are molybdenum, tantalum and zirconium in a mass ratio of 1:1:1;

[0043] The aluminum alloy powder is a mixed powder of aluminum alloy with a particle size of 55 μm and a particle size of 0.5 μm in a mass ratio of 1:0.3;

[0044] The nickel alloy powder is a mixed powder of a nickel alloy having a particle size of 38 μm and a particle size of 5 μm in a mass ratio of 1:0.2;

[0045] S2, fine magnetic powder, isopropyl alcohol, polyvinyl alcohol, zinc stearate, borax, graphite, molybdenum, tantalum, zirconium, aluminum alloy powder, nickel alloy powder, carbon fiber and nano-ceramic particles are mixed uniformly, and then ball milled using a planetary ball mill with a ball-to-material ratio of 5:1, a rotation speed of 300 r / min, and a duration of 90 min;

[0046] S3, placing the powder in a mold in a press, applying a 10000GS magnetic field for pre-magnetization, and dropping the pressure head for cold pressing. The holding time is 2s, and the filling and cold pressing are repeated three times;

[0047] S4, when the vacuum degree is less than 0.01Pa, the mold is heated to 1000℃, then kept warm for 8min, and then cooled to room temperature at a rate of 55℃ / s;

[0048] S5, performing rough grinding and fine grinding on the end face and outer cylindrical surface of the sintered rotor magnetic column, placing the finished rotor magnetic column after grinding in the mold of an injection molding machine, and performing injection molding to obtain a complete motor rotor;

[0049] S6. Place the molded rotor in a 10000GS magnetic field at 55°C for enhanced magnetization, and perform surface deburring on the magnetized rotor to ensure a smooth surface of the finished product.

[0050] Embodiment 3:

[0051] S1. Prepare the following raw materials: 95 parts of fine magnetic powder, 8 parts of isopropyl alcohol, 6 parts of polyvinyl alcohol, 7 parts of zinc stearate, 0.5 parts of borax, 0.5 parts of graphite, 3 parts of rare metals, 8 parts of aluminum alloy powder, 10 parts of nickel alloy powder, 2 parts of carbon fiber, and 14 parts of nano-ceramics;

[0052] The fine magnetic powder was purchased from Baosteel Tiantong Magnetics Co., Ltd.

[0053] The rare metals are molybdenum, tantalum and zirconium in a mass ratio of 1:1:1;

[0054] The aluminum alloy powder is a mixed powder of aluminum alloy with a particle size of 55 μm and a particle size of 0.5 μm in a mass ratio of 1:0.3;

[0055] The nickel alloy powder is a mixed powder of a nickel alloy having a particle size of 38 μm and a particle size of 5 μm in a mass ratio of 1:0.2;

[0056] S2, fine magnetic powder, isopropyl alcohol, polyvinyl alcohol, zinc stearate, borax, graphite, molybdenum, tantalum, zirconium, aluminum alloy powder, nickel alloy powder, carbon fiber and nano-ceramic particles are mixed uniformly, and then ball milled using a planetary ball mill with a ball-to-material ratio of 5:1, a rotation speed of 300 r / min, and a duration of 90 min;

[0057] S3, placing the powder in a mold in a press, applying a 10000GS magnetic field for pre-magnetization, and dropping the pressure head for cold pressing. The holding time is 2s, and the filling and cold pressing are repeated three times;

[0058] S4, when the vacuum degree is less than 0.01Pa, the mold is heated to 1000℃, then kept warm for 8min, and then cooled to room temperature at a rate of 55℃ / s;

[0059] S5, performing rough grinding and fine grinding on the end face and outer cylindrical surface of the sintered rotor magnetic column, placing the finished rotor magnetic column after grinding in the mold of an injection molding machine, and performing injection molding to obtain a complete motor rotor;

[0060] S6. Place the molded rotor in a 10000GS magnetic field at 55°C for enhanced magnetization, and perform surface deburring on the magnetized rotor to ensure a smooth surface of the finished product.

[0061] Embodiment 4:

[0062] The only difference from Example 1 is that the rare metal is only molybdenum.

[0063] Embodiment 5:

[0064] The only difference from Example 1 is that the rare metal is only tantalum.

[0065] Embodiment 6:

[0066] The only difference from Example 1 is that the particle size of the aluminum alloy powder is only 55 μm.

[0067] Embodiment 7:

[0068] The only difference from Example 1 is that the particle size of the nickel alloy powder is only 38 μm.

[0069] Embodiment 8:

[0070] The only difference from Example 1 is that the pre-magnetization in step S3 is not performed;

[0071] Embodiment 9:

[0072] The only difference from Example 1 is that the strong magnetization in step S6 is not performed;

[0073] Comparative Example 1:

[0074] The only difference from Example 1 is that no rare metal is added to the raw materials;

[0075] Comparative Example 2:

[0076] The only difference from Example 1 is that no carbon fiber is added to the raw material;

[0077] Comparative Example 3:

[0078] The only difference from Example 1 is that no nano-ceramics are added to the raw materials;

[0079] Comparative Example 4:

[0080] The only difference from Example 1 is that no aluminum alloy powder and nickel alloy powder are added to the raw materials.

[0081] Table 1: Performance test results of rotors prepared in Examples 1-9 and Comparative Examples 1-4

[0082]

[0083]

[0084] In summary, the high-strength micro-motor rotor of the present invention significantly improves the comprehensive performance of the rotor by optimizing the material formula and manufacturing process. By mixing aluminum alloy powder and nickel alloy powder of different particle sizes, and adding carbon fiber and nano-ceramic particles, the physical strength and rigidity of the rotor are significantly improved. The addition of rare metals further enhances the wear resistance and corrosion resistance of the material, thereby improving the service life of the rotor.

[0085] The parts of the embodiments herein that are not exhaustive of the midpoint values ​​of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.

[0086] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.

[0087] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A high-strength micro motor rotor, characterized in that: The micro motor rotor comprises the following raw materials in parts by mass: 90-95 parts of fine magnetic powder, 7-8 parts of isopropyl alcohol, 5-6 parts of polyvinyl alcohol, 6-7 parts of zinc stearate, 0.4-0.5 parts of borax, 0.3-0.5 parts of graphite, 1.5-3 parts of rare metals, 6-8 parts of aluminum alloy powder, 5-10 parts of nickel alloy powder, 1-2 parts of carbon fiber, and 0.5-14 parts of nano ceramics.

2. According to claim 1, a high-strength micro-motor rotor is characterized in that: The rare metals are molybdenum, tantalum and zirconium in a mass ratio of 1:(0.5-2):(0.5-2).

3. According to claim 1, a high-strength micro-motor rotor is characterized in that: The aluminum alloy powder is a mixed powder of aluminum alloy with a particle size of 50-70 μm and a particle size of 0.5-10 μm in a mass ratio of 1: (0.2-0.4).

4. The high-strength micro-motor rotor according to claim 1, characterized in that: The nickel alloy powder is a mixed powder of nickel alloy with a particle size of 30-40 μm and a particle size of 0.3-15 μm in a mass ratio of 1: (0.1-0.3).

5. A method for preparing a high-strength micro-motor rotor as claimed in claim 1, characterized in that: The method comprises the following steps: S1. Prepare the raw materials according to claim 1; S2, mixing fine magnetic powder, isopropyl alcohol, polyvinyl alcohol, zinc stearate, borax, graphite, molybdenum, tantalum, zirconium, aluminum alloy powder, nickel alloy powder, carbon fiber and nano-ceramic particles uniformly, and then ball milling to obtain powder; S3, pre-magnetizing the powder, then sintering it, and then cooling it to room temperature; S4, finally carry out enhanced magnetization.

6. The method for preparing a high-strength micro-motor rotor according to claim 5, characterized in that: The ball milling process uses a planetary ball mill, wherein the ball-to-material ratio is (3-8):1, the ball milling speed is 250-350r / min, and the time is 80-100min.

7. The method for preparing a high-strength micro-motor rotor according to claim 5, characterized in that: Pre-magnetization is specifically as follows: placing the powder in a mold and applying a magnetic field of 8000-10000GS, and then dropping a pressure head for cold pressing, with a holding time of 1-3s.

8. The method for preparing a high-strength micro-motor rotor according to claim 5, characterized in that: The sintering temperature is 950-110°C and the sintering time is 4-10 minutes.

9. The method for preparing a high-strength micro-motor rotor according to claim 5, characterized in that: In step S3, the cooling rate needs to be controlled at 50-60°C / s.

10. The method for preparing a high-strength micro-motor rotor according to claim 5, characterized in that: During the enhanced magnetization process, a magnetic field of 10000-12000GS is applied for 5-10s at a temperature of 50-60°C.